Stable Protein Sialylation in Physcomitrella - Bohlender, Lennard L.; Parsons, Juliana; Hoernstein, Sebastian N. W.; Rempfer, Christine; Ruiz-Molina, Natalia; Lorenz, Timo; Rodríguez Jahnke, Fernando; Figl, Rudolf; Fode, Benjamin; Altmann, Friedrich; Reski, Ralf; Decker, Eva L. (Frontiers in Plant Science, 2020)
Recombinantly produced proteins are indispensable tools for medical applications. Since the majority of them are glycoproteins, their N-glycosylation profiles are major determinants for their activity, structural properties and safety. For therapeutical applications, a glycosylation pattern adapted to product and treatment requirements is advantageous. Physcomitrium patens (Physcomitrella, moss) is able to perform highly homogeneous complex-type N-glycosylation. Additionally, it has been glyco-engineered to eliminate plant-specific sugar residues by knock-out of the β1,2-xylosyltransferase and α1,3-fucosyltransferase genes (Δxt/ft). Furthermore, Physcomitrella meets wide-ranging biopharmaceutical requirements such as GMP compliance, product safety, scalability and outstanding possibilities for precise genome engineering. However, all plants, in contrast to mammals, lack the capability to perform N-glycan sialylation. Since sialic acids are a common terminal modification on human N glycans, the property to perform N-glycan sialylation is highly desired within the plant-based biopharmaceutical sector. In this study, we present the successful achievement of protein N-glycan sialylation in stably transformed Physcomitrella. The sialylation ability was achieved in a Δxt/ft moss line by stable expression of seven mammalian coding sequences combined with targeted organelle-specific localization of the encoded enzymes responsible for the generation of β1,4 galactosylated acceptor N glycans as well as the synthesis, activation, transport and transfer of sialic acid. Production of free (Neu5Ac) and activated (CMP-Neu5Ac) sialic acid was proven. The glycosidic anchor for the attachment of terminal sialic acid was generated by the introduction of a chimeric human β1,4 galactosyltransferase gene under the simultaneous knock-out of the gene encoding the endogenous β1,3 galactosyltransferase. Functional complex-type N-glycan sialylation was confirmed via mass spectrometric analysis of a stably co-expressed recombinant human protein.